Tecia solanivora, Povolny (Lepidoptera: Gelechiidae): a Review of its Origin, Dispersion and Biological Control Strategies (2013)
In 1956, Tecia solanivora was reported by the first time in Central America. This Lepidopteran insect of the Gelechiidae family was found to severely damage potato crops (Solanum tuberosum), which adversely affected local economy. Although this insect has reduced mobility, it has invaded several countries in Central and South America as well as the Canary Islands in Spain. The damage caused by T. solanivora has been detected in both field crops and stored tubers. The economic impact of the pest in countries of the Andean area is much more serious than in Central America, mainly because potato is an important family staple and production is very intensive. Therefore, T. solanivora is considered the most damaging crop insect pest in such countries. This review focuses on the actual scientific knowledge on T. solanivora, which includes its origin and spread across different countries, implications, strategies for controlling its impact. In addition, current knowledge generated from phylogeography and population genetics of T. solanivora are discussed as complementary strategies to deal with this pest.